Facile enantioselective synthesis of (S)-N-(5-chlorothiophene-2-sulfonyl)-beta,beta-diethylalaninol via proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination of aldehyde - Rawat, Varun; Chouthaiwale, Pandurang V.; Chavan, Vilas B.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A high-yielding enantioselective synthesis of the bioactive (S)-N-(5-chlorothiophene-2-sulfonyl)beta,beta-diethylalaninol (1), a Notch-1-sparing gamma-secretase inhibitor metabolite (with EC50 = 28 nM) effective in reduction of All production in vivo, has been realized starting from readily available 3-pentanone. The key steps of the synthesis are proline-catalyzed alpha-aminooxylation and alpha-amination of aldehyde: the latter contributing an overall yield of 45.2% and 98% ee. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; alpha-Aminooxylation; Alzheimer's disease; Amino alcohol; Proline